2019
DOI: 10.1253/circrep.cr-18-0009
|View full text |Cite
|
Sign up to set email alerts
|

Low Activities of Daily Living Associated With Increased Cardiovascular Disease Mortality in Japan ― Analysis of Health Records From a Nationwide Claim-Based Database, JROAD-DPC ―

Abstract: Background: The aim of this study was to clarify the clinical impact of activities of daily living (ADL) using the J apanese R egistry o f A ll Cardiac and Vascular D iseases-Diagnosis Procedure Combination (JROAD-DPC) database. Methods and Results: From April 2012 to March 2014, the JROAD-DPC database included 206,643 patients with acute coronary syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Moreover, HAD was associated with worse clinical outcomes after adjusting for the MAGGIC risk score. These findings suggest that assessment of functional status trajectory during hospitalization is important for risk stratification in elderly patients with HF 17 …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, HAD was associated with worse clinical outcomes after adjusting for the MAGGIC risk score. These findings suggest that assessment of functional status trajectory during hospitalization is important for risk stratification in elderly patients with HF 17 …”
Section: Resultsmentioning
confidence: 85%
“…These findings suggest that assessment of functional status trajectory during hospitalization is important for risk stratification in elderly patients with HF. 17 Elderly patients with HF show a different clinical profile compared with younger patients. 18 Generally, elderly patients with HF are more likely to be female and have HFpEF with a more complex pattern.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that higher NT-proBNP levels were associated with higher incidences of all-cause mortality [ 36 ], which is consistent with our study. Dunlay et al reported that mortality increased with increasing ADL difficulty [ 37 ] and low admission ADL was reported to be associated with cardiovascular mortality [ 38 ]. In this study, low ADL was a predictor for all-cause mortality and patients with high risk of all-cause mortality more often had low ADL at both admission and discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using the administrative database, this study focused mainly on patients exposed to drugs that inhibit gastric acid secretion, based on previous epidemiological research for stroke and bleeding events [45]. Although we adjusted for some confounding factors using the IPTW method in the subgroup analysis, other potential risk factors shown in the previous research (such as bleeding risk score) will need to be identified and collected in future research [46][47][48]. As the current study design does not permit accurate assessment of multiple outcomes (as each outcome requires consideration of a different profile of potential confounding factors in order to minimize bias), there is value in conducting future comparisons of vonoprazan and PPIs to assess their relative effect on medical costs (including hospitalization costs) related to gastrointestinal bleeding, cardiovascular outcomes, and mortality (which are critical endpoints for IHD patients, although their assessment will require a larger sample size), and complications associated with acid-suppressive drugs.…”
Section: Discussionmentioning
confidence: 99%